PEMIKIRAN PENDIDIKAN AL-GHAZALI - ALWIZAR ALWIZAR (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Al-Ghazali is great Islamic expert who masters the several disiplines. He does not only master the Islamic knowledge, but also the philosophy and finally be chooses Tasawuf and Mystic. According to Philip K. Hitti, Al-Ghazali is one of the significant persons in Islamic history and Muslim communities. His capability in expressing the ideas is know original, critacal and communacative. Ignaz Golgziher acknowledged that Al-Ghazali has given the big effect and impact in the historicity of Islamic thought and the religiosity of Muslim who is know as an Islamic encyclopedia and master almost the entire of knowledge of the different disiplines. In Education, Al-Ghazali also has analyzed the various aspects of education, such as: the role, purpose, curriculum, method of education and teachers and students ethics. Al-Ghazali‟s educational thought still gives many inspiration toward the educational thought in the world, Islam and Muslims of Sunni.